2021
DOI: 10.1097/pcc.0000000000002787
|View full text |Cite
|
Sign up to set email alerts
|

ICU Admission in Children With Acute Lymphoblastic Leukemia in Sweden: Prevalence, Outcome, and Risk Factors

Abstract: OBJECTIVES: Despite progress in the treatment of childhood acute lymphoblastic leukemia, severe complications are common, and the need of supportive care is high. We explored the cumulative prevalence, clinical risk factors, and outcomes of children with acute lymphoblastic leukemia, on first-line leukemia treatment in the ICUs in Sweden. DESIGN:A nationwide prospective register and retrospective chart review study. SETTING:Children with acute lymphoblastic leukemia were identified,and demographic and clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Admissions not identified by chart review and lacking questionnaire data were shorter, occurred later after the AML diagnosis and were more often attributed to observational character than those with questionnaire data, suggesting missing notes in patient charts for short observations, possibly partly due to separate journal system used by ICUs or intensive care outside university hospitals. Our study in children with acute lymphoblastic leukaemia (ALL) showed a similar discrepancy in registration 12 . This finding of discrepancy highlights the importance of data source in studies on ICU care.…”
Section: Discussionsupporting
confidence: 52%
“…Admissions not identified by chart review and lacking questionnaire data were shorter, occurred later after the AML diagnosis and were more often attributed to observational character than those with questionnaire data, suggesting missing notes in patient charts for short observations, possibly partly due to separate journal system used by ICUs or intensive care outside university hospitals. Our study in children with acute lymphoblastic leukaemia (ALL) showed a similar discrepancy in registration 12 . This finding of discrepancy highlights the importance of data source in studies on ICU care.…”
Section: Discussionsupporting
confidence: 52%
“…Some data that may be important for prognosis were not collected, including inotrope requirements, specific organ scores within PELOD, diagnosis of sepsis, neutropenia, timing during cancer therapy, disease status and stage, contents of and response to chemotherapy, hematopoietic stem cell transplantation, and type of leukemia or lymphoma. 1,17,18 Some of the variables collected occurred only rarely, for example, neurological diagnosis (2.8%), recovery from a surgical procedure (6.4%), ECMO (0.9%), HFOV (3.7%), iNO (7.3%), and RISC over 4 (3%), preventing their inclusion in the multiple regression models (we included only variables occurring in at least 5% of survivors and nonsurvivors). The lower mortality in our cohort than in previous cohorts may be due to general improvements in oncology and ICU care over time; however, we cannot be more specific given the limitations in our data set.…”
Section: Discussionmentioning
confidence: 99%
“…These treatment protocols are however, associated with severe side effects. Infections and treatment-related toxicity conditions are leading causes for of mortality and morbidity in cancer patients that require treatment in the intensive care unit and 2% to 28% of the pediatric cancer patients have been shown to require admission to the PICU during their disease course (2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%